Cutaneous Leishmaniasis Caused by Leishmania infantum, Israel, 2018–2021 - Michal Solomon; Nadav Astman; Karin Warshavsky; Aviv Barzilai; Tal Meningher; Dror Avni; Eli Schwartz (Emerging Infectious Diseases, 2023)
Cutaneous leishmaniasis (CL) is endemic to Israel. Previously, CL caused by Leishmania infantum had been reported in Israel only once (in 2016). We report 8 L. infantum CL cases; 7 occurred during 2020–2021. None of the patients had systemic disease. L. infantum CL may be an emerging infection in Israel.